Applied Research On Design Of Smart Clothing Base On Thermochromic Material - Sun, Liushuang; Chen, Shuqin; Gu, Zhujun; Luo, Yue; Hu, Yue (Advances in Social Sciences Research Journal, 2017)
As people having a higher living standard, customers requires higher level on smart clothing. People transfer their attentions from practicality to scientificalness based on the requirement of the color of clothes. Therefore, according to the theory that colors change when lights and temperature change, Thermochromic material that made from chromotropic dyes and chromotropic fibers get widely used in the smart clothing industry. This paper will disclose the research of the design and application of smart clothing based on the study of Thermochromic material.